Evaluation of mortality rate among ICU patients in university hospitals of Tehra - Majid, Vatankhah; Hamidreza, Sharifnia; Arezoo, Ahmadi; Mojtaba, Mojtahedzadeh; Atabak , Najafi (International Journal of Psychosocial Rehabilitation, 2020)
Objective: One of the challenging issues in the intensive care unit, in addition to controlling mortality, is the identification of effective factors in this area. Previous studies have found many causes, including diagnosis of disease, age, chronic health status and physiological indicators, in terms of mortality. However, there are disagreements about the causes of death. In this study, we have tried to investigate the causes and factors affecting mortality in Tehran hospitals. Data Sources: In this cross-sectional and retrospective study, mortality rate and its risk factors were evaluated in intensive care units in university hospitals in Tehran. Study Selection: This study was conducted in 2011-2015 years in 12857 patients. In this study age, sex, duration of hospitalization in ICU, cause of hospitalization, underlying disease, date of discharge or death, cause of death, type of ICU and APACHE score. Data Extraction: The results of the study showed that the highest mortality rate was in men (p = 0.001). Data Synthesisthere was a direct correlation between mortality rates and segments of closed ICU, duration of admission, cause of hospitalization, aphasia score of patients, while there was no significant relationship between age and mortality (P = 0.8) Conclusions: The results of this study were consistent with many previous studies, but the mortality rate with the high level of the statistical society has been less frequent than previous studies. However, the need for study in different populations is needed to achieve better results.